2011
DOI: 10.1016/j.ajpath.2011.05.031
|View full text |Cite
|
Sign up to set email alerts
|

Tumor-Recruited Neutrophils and Neutrophil TIMP-Free MMP-9 Regulate Coordinately the Levels of Tumor Angiogenesis and Efficiency of Malignant Cell Intravasation

Abstract: Tumor-associated neutrophils contribute to neovascularization by supplying matrix metalloproteinase-9 (MMP-9), a protease that has been genetically and biochemically linked to induction of angiogenesis. Specific roles of inflammatory neutrophils and their distinct proMMP-9 in the coordinate regulation of tumor angiogenesis and tumor cell dissemination, however, have not been addressed. We demonstrate that the primary tumors formed by highly disseminating variants of human fibrosarcoma and prostate carcinoma re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
233
1
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 260 publications
(244 citation statements)
references
References 52 publications
3
233
1
1
Order By: Relevance
“…33 Recently, Bekes et al showed that tumor-associated neutrophils played a critical role in tumor angiogenesis and migration of tumor cells through secretion of TIMP-free MMP-9. 34 They also showed that the enhancement of angiogenesis was blocked by inhibition of neutrophil recruitment. Furthermore, Benelli et al showed that depletion of neutrophils intensively inhibited cytokine-induced angiogenesis in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…33 Recently, Bekes et al showed that tumor-associated neutrophils played a critical role in tumor angiogenesis and migration of tumor cells through secretion of TIMP-free MMP-9. 34 They also showed that the enhancement of angiogenesis was blocked by inhibition of neutrophil recruitment. Furthermore, Benelli et al showed that depletion of neutrophils intensively inhibited cytokine-induced angiogenesis in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…One mechanism neutrophils employ to promote tumor growth is the induction of angiogenesis (Figure 3), and neutrophil depletion decreased tumor growth and microvessel density in both transplantable and spontaneous tumor models 65,85,91,[120][121][122][123] . Blocking CXCR2 signaling or transplanting cancer cell lines into CXCR2-deficient mice recapitulated these effects 58,124,125 .…”
Section: Neutrophils and Tumor Growthmentioning
confidence: 99%
“…IL-8 is another chemokine expressed in variety of tumors and is associated with neutrophil recruitment and activation [251]. For example, IL-8 secreted by human fibrosarcoma and prostate carcinoma cells promoted the infiltration of MMP-9 + neutrophils [252] and melanoma secreted IL-8 was shown to increase CD11b/CD18 expression on neutrophils, an indication for their activation [253,254].…”
Section: Neutrophil Activation In Cancermentioning
confidence: 99%
“…TANs were shown to support tumor growth by producing angiogenic factors and matrix-degrading enzymes [8,57,64,252,264,277]. Neutrophils were also shown to promote the acquisition of a metastatic phenotype [265] and to suppress antitumor immune responses [278].…”
Section: Neutrophils At the Primary Tumor Sitementioning
confidence: 99%